Comparative Assessment of Familiarity/Novelty Preferences in Rodents - Beery, Annaliese K.; Shambaugh, Katharine L. (Frontiers in Behavioral Neuroscience, 2021)
Sociality—i.e., life in social groups—has evolved many times in rodents, and there is considerable variation in the nature of these groups. While many species-typical behaviors have been described in field settings, the use of consistent behavioral assays in the laboratory provides key data for comparisons across species. The preference for interaction with familiar or novel individuals is an important dimension of social behavior. Familiarity preference, in particular, may be associated with more closed, less flexible social groups. The dimension from selectivity to gregariousness has been used as a factor in classification of social group types. Laboratory tests of social choice range from brief (10 minutes) to extended (e.g., 3 hours). As familiarity preferences typically need long testing intervals to manifest, we used 3-hour peer partner preference tests to test for the presence of familiarity preferences in same-sex cage-mates and strangers in rats. We then conducted an aggregated analysis of familiarity preferences across multiple rodent species (adult male and female rats, mice, prairie voles, meadow voles, and female degus) tested with the same protocol. We found a high degree of consistency within species across data sets, supporting the existence of strong, species-typical familiarity preferences in prairie voles and meadow voles, and a lack of familiarity preferences in other species tested. Sociability, or total time spent near conspecifics, was unrelated to selectivity in social preference. These findings provide important background for interpreting the neurobiological mechanisms involved in social behavior in these species.